Development and Physicochemical Characterization of a pH and Thermo-Responsive Fusidic Acid-Loaded Polymeric Nanogel against Skin Infections - Hassan Ali; Azizullah Mukhtar; Umar Farooq; Shafi Ullah; Muhammad Tariq Khan; Tayyaba Zulfiqar; Izhar Ullah; Muhammad Farhan Ali Khan (Journal of Pharmaceutical Innovation, 2027)

Leachate pollution pathways in an arid coastal megacity: salinity, organics, and LPI–GIS mapping for Karachi - Azizullah Channa; Muhammad Yousuf Jat Baloch; Rasool Bux Mahar; Hongtao Wang (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Outcomes of linezolid, glycopeptides, and other regimens in ampicillin-resistant, vancomycin-susceptible and vancomycin-resistant enterococcal bacteremia in a resource-limited setting: stewardship implications - Yameena Noman Khan; Ali Mala; Rubab Murtaza; Irshad Batool; Azizullah Khan; Imtiaz Begum; Jamil Muqtadir; Abdul Rasheed; Sameeullah Bhatti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Enterococcal bloodstream infections (BSI) are associated with high morbidity and limited treatment options, particularly in resource-limited settings where access to standard agents may be constrained. Comparative effectiveness data directly informing the choice among available agents for both vancomycin-resistant (VRE) and ampicillin-resistant, vancomycin-susceptible (VSE) enterococcal bacteremia are specifically lacking in such settings, where regimen selection is frequently dictated by drug availability and cost rather than guideline preference. We conducted a retrospective cohort study across three hospitals of a single university health system (Dr. Ziauddin University, Karachi, Pakistan) including hospitalized adults (≥ 18 years) with clinically significant enterococcal bacteremia (a positive blood culture together with clinical evidence of infection, as adjudicated by the treating physician) between January 1, 2010, and May 31, 2025. Only the first episode per patient was analyzed. VRE and VSE cohorts were compared for baseline characteristics and empiric therapy. Definitive monotherapy—receipt of a single study agent active against the isolate, assigned within the prespecified 48- to 72-h window after index blood culture (time-zero), by which time organism identification and susceptibility results were generally available—was assessed within the VRE and VSE cohorts. Because discharge alive is a competing event for in-hospital death, cumulative incidence functions (CIF) with Gray’s test and an adjusted Fine–Gray competing-risks model (adjusted for age, Charlson Comorbidity Index, qPitt score, septic shock, and definitive antibiotic exposure (vancomycin, teicoplanin, daptomycin, tigecycline)) were used. Of 925 screened patients, 501 met inclusion criteria (VSE n = 404; VRE n = 97). VRE bacteremia presented with greater acute severity (higher APACHE II) and was more frequently catheter-associated, while VSE more often had urinary and intra-abdominal sources (all p < 0.001). In definitive monotherapy analyses among VRE ( n = 67; tigecycline excluded, as it was used only as salvage therapy), 28-day mortality was numerically higher with teicoplanin (66.7%) but did not differ significantly across linezolid, teicoplanin, and daptomycin; CIF analysis similarly showed no difference in cumulative incidence of in-hospital death (Gray’s p = 0.246). Tigecycline, used only as salvage therapy, was associated with higher 28-day mortality (80.0% vs 47.8%; p = 0.003; Supplementary Table S1). In VSE monotherapy ( n = 404), teicoplanin exposure was associated with higher ICU admission and higher 28-day mortality, and CIF curves differed across vancomycin, teicoplanin, and linezolid (Gray’s p < 0.001); however, the linezolid-exposed group had sparse/zero events for several endpoints, suggesting confounding by indication. In the adjusted Fine–Gray model, higher qPitt score was independently associated with mortality (sHR 2.21, 95% CI 1.62–3.01; p < 0.001). Tigecycline (sHR 4.00, 95% CI 2.11–7.60; p < 0.001) and daptomycin exposure (sHR 3.11, 95% CI 1.37–7.07; p = 0.007) were associated with higher subdistribution hazard of death, whereas vancomycin exposure was associated with lower hazard (sHR 0.36, 95% CI 0.20–0.67; p = 0.001). In this multi-hospital, single-system cohort, VRE bacteremia was more severe and more often catheter-associated than VSE. When accounting for discharge as a competing event, mortality differences across definitive monotherapy groups were not significant in VRE, while VSE comparisons were influenced by treatment selection and sparse outcome counts in some groups. Severity (qPitt score) was a key independent predictor of mortality, and observed antibiotic–mortality associations should be interpreted cautiously given confounding by indication.

Hydrobiological Studies in Kalmat Khor, a Coastal Lagoon on Balochistan Coast (Northern Arabian Sea) - Qadeer Mohammad Ali; Azizullah Baloch; Quratulan Ahmed; Levent Bat (Thalassas: An International Journal of Marine Sciences, 2026)

First Study on the Fish Fauna and Fisheries Resources of Kalmat Khor - A Coastal Lagoon on Balochistan Coast, Pakistan (Northern Arabian Sea) - Qadeer Mohammad Ali; Azizullah Baloch; Quratulan Ahmed; Orçin Uygun; Levent Bat (Thalassas: An International Journal of Marine Sciences, 2026)

Integrated Electrocoagulation and Adsorption Strategy for the Treatment of Fresh Landfill Leachate - Azizullah Channa; Munawar Ali Pinjaro; Rasool Bux Mahar; Hongtao Wang (Water, Air, & Soil Pollution, 2026)

Modeling and experimental validation of backwash optimization in ultra low pressure reverse osmosis membrane (ULPRO) system for brackish water treatment - Azizullah Hanif; Mohd Usman Mohd Junaidi; Mohd Azlan Hussain (Journal of Water Process Engineering, 2025)

Survey and seasonal abundances of major insect pest species in the maize fields of Punjab, Pakistan - Naveed Akhtar; Hafiz Muhammad Tahir; Azizullah; Aamir Ali; Rabia Fajar; Ayesha Muzamil; Reham Fathy; Hend O. Mohamed; Dilawar Abbas (International Journal of Tropical Insect Science, 2025)

Performance evaluation of DME-CO2 huff-n-puff and continuous DME injection in heavy oil reservoirs through numerical simulation - Allah Bakhsh; Ren Shaoran; Azizullah Shaikh; Syed Jamal ud din; Zeeshan Khan; Imtiaz Ali; Zhang Liang (Modeling Earth Systems and Environment, 2024)

Soil Rhizosphere pH, Enzymatic and Microbial Activities Under Different Nitrogen and Sulfur Fertilization of Soybean (Glycine max L.) - Azizullah Khalili; Aketi Ramesh; Mahaveer P. Sharma (Journal of Soil Science and Plant Nutrition, 2024)

Novel structures and evolution of tRNA genes: insight into the chloroplast tRNAs of family Sapindaceae - Khurram Shahzad; Zhong-Hu Li; Hanif Khan; Azizullah Aziullah; Umar Zeb; Fengjie Cui; Junhu Dai; Saleha Ashfaq; Sajid Fiaz; Eman A. Mahmoud; Ihab Mohamed Moussa; Hosam O. Elansary (Genetic Resources and Crop Evolution, 2024)

How Good Is Online Information for Patients on the Treatment for Luminal Gastrointestinal Cancers? A Comprehensive Evaluation in English and Spanish - Renato Beas; Cielo Cabanillas-Ramirez; Diego Izquierdo-Veraza; Andres Chapoñan-Lavalle; Dalton Norwood; Karina Sato-Espinoza; Adrian Riva-Moscoso; Isabella Ribaudo; Mirian Ramirez-Rojas; Azizullah Beran; Eleazar E. Montalvan-Sanchez (Journal of Cancer Education, 2023)

Genome-wide identification and expression analysis of U-box gene family in Juglans regia L. - Hanif Khan; Umar Zeb; Sadaf Gul; Azizullah Aziziullah; Naushad Ali; Sajid Fiaz; Asmaa M. Abushady; Shariat Ullah; Salar Muhammad; Kotb A. Attia; Itoh Kimiko; Fengjie Cui; et al. (Genetic Resources and Crop Evolution, 2023)

Population genetics informs new insights into the phytogeographic history of Juglans regia L. - Hanif Khan; Irfan Ullah; Keith Woeste; Sajid Fiaz; Umar Zeb; Abdelhalim I. Ghazy; Azizullah Azizullah; Salma Shad; Maria E. Malvolti; Ming Yue; Kotb A. Attia; Arif A. Mohammed; et al. (Genetic Resources and Crop Evolution, 2023)

Elucidating growth and biochemical characteristics of rice seedlings under stress from chromium VI salt and nanoparticles - Maryam Noor; Arif Ullah; Muhammad Israr Khan; Irum Raza; Muhammad Iqbal; Abdul Aziz; Gil Won Kim; Nadia Taimur; Azizullah Azizullah; Imran Ali; Pil Joo Kim (Environmental Science and Pollution Research, 2023)

Microbe-oriented nanoparticles as phytomedicines for plant health management: An emerging paradigm to achieve global food security - Muhammad Noman; Temoor Ahmed; Usman Ijaz; Amir Hameed; Muhammad Shahid; Azizullah; Dayong Li; Fengming Song (Critical Reviews in Food Science and Nutrition, 2023)

A modified experimental approach to determine formation porosity from rock cuttings - Semab Tariq; Zeeshan Khan; Allah Bakhsh; Syed Jamal ud Din; Azizullah Shaikh; Habib Ur Rehman; Rashid Sher Muhammad; Liang Zhang (Arabian Journal of Geosciences, 2023)

Variations in the Behaviour, Survival, Haematology, and Biochemistry of Ctenopharyngodon idella (Grass Carp) After Exposure to Commercial Grade Atrazine - Syed Ata Ur Rahman Shah; Muhammad Rauf; Shandana Ali; Sana Ullah; Kalim Ullah; Syed Ishtiaq Anjum; Azizullah Azizullah; Farman Ullah Dawar (Bulletin of Environmental Contamination and Toxicology, 2023)

Correction: Comparative studies of enhancing oil recovery optimization for optimum oil feld development - Muhammad Usman Tahir; Hongtao Zhou; Bilal Shams Memon; Wei David Liu; Asadullah Memon; Azizullah Shaikh; Danish Khan; Allah Bakhsh (Modeling Earth Systems and Environment, 2023)

Screening of various Brassica species for phytoremediation of heavy metals-contaminated soil of Lakki Marwat, Pakistan - Iftikhar Ali; Muhammad Jamil Khan; Azizullah Shah; Farah Deeba; Haziq Hussain; Fazal Yazdan; Mati Ullah Khan; Muhammad Daud Khan (Environmental Science and Pollution Research, 2022)

The approach of dimethyl ether-enhanced waterflooding (DEW) for oil recovery: a review - Allah Bakhsh; Liang Zhang; Huchao Wei; Azizullah Shaikh; Nasir khan; Saeed Khan; Ren Shaoran (Arabian Journal of Geosciences, 2022)

Nano-suspension combined effect with polymer gels for enhanced oil recovery in low permeability reservoir - Imran Akbar; Hongtao Zhou; Wei Liu; Abdul Sami Qureshi; Asadullah Memon; Temoor Muther; Ubedullah Ansari; Muhammad UsmanTahir; Allah Bakhsh; Azizullah Shaikh; Habibou Hamed Hamed (Arabian Journal of Geosciences, 2021)

Does ICT lessen CO2 emissions for fast-emerging economies? An application of the heterogeneous panel estimations - Faisal Faisal; Azizullah; Turgut Tursoy; Ruqiya Pervaiz (Environmental Science and Pollution Research, 2020)

Responses of morphological, physiological, and biochemical characteristics of maize (Zea mays L.) seedlings to atrazine stress - Shagufta Bibi; Sarzamin Khan; Nadia Taimur; Muhammad K. Daud; Azizullah Azizullah (Environmental Monitoring and Assessment, 2019)

Bio-assessment and remediation of arsenic (arsenite As-III) in water by Euglena gracilis - Sidra Tahira; Sarzamin Khan; Samrana Samrana; Lubna Shahi; Imran Ali; Waheed Murad; Zia ur Rehman; Azizullah Azizullah (Journal of Applied Phycology, 2019)

Phytotoxic effects of two commonly used laundry detergents on germination, growth, and biochemical characteristics of maize (Zea mays L.) seedlings - Syeda Uzma; Sarzamin Khan; Waheed Murad; Nadia Taimur; Azizullah Azizullah (Environmental Monitoring and Assessment, 2018)

Use of various biomarkers to explore the effects of GSM and GSM-like radiations on flowering plants - Muhammad Daud Khan; Shafaqat Ali; Azizullah Azizullah; Zhu Shuijin (Environmental Science and Pollution Research, 2018)

Pesticide-induced oxidative stress and antioxidant responses in tomato (Solanum lycopersicum) seedlings - Shakirullah Khan Shakir; Shahid Irfan; Basreen Akhtar; Shafiq ur Rehman; Muhammad Khan Daud; Nadia Taimur; Azizullah Azizullah (Ecotoxicology, 2018)

Ecotoxicological evaluation of two anti-dandruff hair shampoos using Lemna minor - Azizullah Azizullah; Shakirullah Khan Shakir; Shahana Shoaib; Halima Bangash; Nadia Taimur; Waheed Murad; Muhammad Khan Daud (Environmental Monitoring and Assessment, 2018)

Marble industry effluents cause an increased bioaccumulation of heavy metals in Mahaseer (Tor putitora) in Barandu River, district Buner, Pakistan - Shahi Mulk; Abdul Latif Korai; Azizullah Azizullah; Lubna Shahi; Muhammad Nasir Khan Khattak (Environmental Science and Pollution Research, 2017)

Mix cropping of legume (Vigna Radiata) and non-legume (Zea Mays) crops alleviates water stress as revealed by growth and biochemical parameters - Kalim Ullah Khan; Waheed Murad; Azizullah Azizullah; Hazir Rahman; Muhammad Daud Khan (Acta Physiologiae Plantarum, 2017)

Leaf-based physiological, metabolic, and ultrastructural changes in cultivated cotton cultivars under cadmium stress mediated by glutathione - M. K. Daud; Lei Mei; Azizullah Azizullah; Muhammad Dawood; Imran Ali; Qaisar Mahmood; Waheed Ullah; Muhammad Jamil; S. J. Zhu (Environmental Science and Pollution Research, 2016)

Effects of industrial wastewater on growth and biomass production in commonly grown vegetables - Syeda Uzma; Azizullah Azizullah; Roqaia Bibi; Farhat Nabeela; Uzair Muhammad; Imran Ali; Zia Ur Rehman; Donat-Peter Häder (Environmental Monitoring and Assessment, 2016)

Alleviation of lead-induced physiological, metabolic, and ultramorphological changes in leaves of upland cotton through glutathione - Mumtaz Khan; M. K. Daud; Ali Basharat; Muhammad Jamil Khan; Azizullah Azizullah; Niaz Muhammad; Noor Muhammad; Zia ur Rehman; Shui Jin Zhu (Environmental Science and Pollution Research, 2016)

Effect of some commonly used pesticides on seed germination, biomass production and photosynthetic pigments in tomato (Lycopersicon esculentum) - Shakirullah Khan Shakir; Memoona Kanwal; Waheed Murad; Zia ur Rehman; Shafiq ur Rehman; M. K. Daud; Azizullah Azizullah (Ecotoxicology, 2016)

Decreased fish diversity found near marble industry effluents in River Barandu, Pakistan - Shahi Mulk; Abdul Latif Korai; Azizullah Azizullah; Muhammad Nasir Khan Khattak (Ecotoxicology, 2016)

Phytotoxicity evaluation of some commonly used shampoos using Brassica napus L. - Faiqa Naeem; Faiza Ahmed; Memoona Kanwal; Waheed Murad; Azizullah Azizullah (Environmental Science and Pollution Research, 2015)

Effects of long-term exposure to industrial wastewater on photosynthetic performance of Euglena gracilis measured through chlorophyll fluorescence - Azizullah Azizullah; Peter Richter; Donat-Peter Häder (Journal of Applied Phycology, 2015)

Impact of marble industry effluents on water and sediment quality of Barandu River in Buner District, Pakistan - Shahi Mulk; Azizullah Azizullah; Abdul Latif Korai; Muhammad Nasir Khan Khattak (Environmental Monitoring and Assessment, 2015)

Microbial contamination of drinking water in Pakistan—a review - Farhat Nabeela; Azizullah Azizullah; Roqaia Bibi; Syeda Uzma; Waheed Murad; Shakirullah Khan Shakir; Waheed Ullah; Muhammad Qasim; Donat-Peter Häder (Environmental Science and Pollution Research, 2014)

Determination of heavy metal contents in water, sediments, and fish tissues of Shizothorax plagiostomus in river Panjkora at Lower Dir, Khyber Pakhtunkhwa, Pakistan - Kabir Ahmad; Azizullah Azizullah; Shama Shama; Muhammad Nasir Khan Khattak (Environmental Monitoring and Assessment, 2014)

Fast bioassessment of wastewater and surface water quality using freshwater flagellate Euglena gracilis—a case study from Pakistan - Azizullah Azizullah; Muhammad Jamil; Peter Richter; Donat-Peter Häder (Journal of Applied Phycology, 2014)

Ecotoxicity evaluation of a liquid detergent using the automatic biotest ECOTOX - Azizullah Azizullah; Peter Richter; Waheed Ullah; Imran Ali; Donat-Peter Häder (Ecotoxicology, 2013)

Chronic toxicity of a laundry detergent to the freshwater flagellate Euglena gracilis - Azizullah Azizullah; Peter Richter; Muhammad Jamil; Donat-Peter Häder (Ecotoxicology, 2012)

Sensitivity of various parameters in Euglena gracilis to short-term exposure to industrial wastewaters - Azizullah Azizullah; Peter Richter; Donat-Peter Häder (Journal of Applied Phycology, 2012)

Responses of morphological, physiological, and biochemical parameters in Euglena gracilis to 7-days exposure to two commonly used fertilizers DAP and urea - Azizullah Azizullah; Peter Richter; Donat-Peter Häder (Journal of Applied Phycology, 2012)

Comparative toxicity of the pesticides carbofuran and malathion to the freshwater flagellate Euglena gracilis - Azizullah Azizullah; Peter Richter; Donat-Peter Häder (Ecotoxicology, 2011)